Positron Emission Tomography with Computed Tomography (PET/CT) - Santiago, Jonas Francisco Y. (Springer International Publishing : Imprint: Springer, 2015)
Positron Emission Tomography with Computed Tomography (PET/CT)  is an accessible case book presenting interesting cases encountered  by the author over the last ten years experience as the chairman and director of the only PET Center in the Philippines. It aims to guide physicians in the accurate interpretation of the PET scans of uncommon diseases, and sometimes common cases but in extraordinary situations or conditions.   Encompassing a wide and varied range of fields such as oncology, inflammatory, immunology, anatomic variants etc., Positron Emission Tomography with Computed Tomography (PET/CT)  will help those beginning their practice, and may even be useful to veterans of the field whose scope of practice has been limited to more common indications of an FDG-PET scan.